Application of the AHP-TOPSIS Method As Best Employee Decision Support System - Nunung Nurmaesah; Detin Sofia; Savitri Octavia (JURNAL SISFOTEK GLOBAL, 2023)
In every company, employees are an essential element. To be able to find out whether employees are competent or not, an employee performance appraisal is needed. Employee appraisal is critical, not only because it is a determining factor in employee wage increases and promotions but also because it can evaluate skills. However, the current employee appraisal process still needs to be more objective and accurate, and it takes a long time, and there are many possibilities for human error. This study aims to design a decision support system in determining the best employees using the Analytical Hierarchy Process (AHP) and Technique for Order Preference by Similarity to Ideal Solution (TOPSIS) methods. The AHP method is used to calculate the weight of each parameter, and TOPSIS is used to perform the ranking process based on the parameter weighting results. The results of this study found that the best employees were employees with the alternative code A3, with a value of 0.74271.